The impact of study factors in the association of periodontal disease and cognitive disorders: systematic review and meta-analysis. (14th February 2023) - Larvin, Harriet; Gao, Chenyi; Kang, Jing; Aggarwal, Vishal R; Pavitt, Susan; Wu, Jianhua
Abstract: Aim: The aim was to assess study factors that impact the association of cognitive disorders in people with periodontal disease (PD). Method: Medline, EMBASE and Cochrane databases were searched until February 2022 using keywords and MeSH: (periodon * OR tooth loss OR missing teeth) AND (dementia OR Alzheimer's Disease OR cognitive * ). Observational studies reporting prevalence or risk of cognitive decline, dementia or Alzheimer's disease (AD) in people with PD compared with healthy controls were included. Meta-analysis quantified the prevalence and risk (relative risk[RR]) of cognitive decline, dementia/AD, respectively. Meta-regression/subgroup analysis explored the impact of study factors including PD severity and classification type, and gender. Results: Overall, 39 studies were eligible for meta-analysis: 13 cross-sectional and 26 longitudinal studies. PD demonstrated increased risks of cognitive disorders (cognitive decline—RR = 1.33, 95% CI = 1.13–1.55; dementia/AD—RR = 1.22, 95% CI = 1.14–1.31). Risk of cognitive decline increased with PD severity (moderate—[RR] = 1.14, 95% confidence interval [CI] = 1.07–1.22; severe—RR = 1.25, 95% CI = 1.18–1.32). For every 10% population increase in females, the risk of cognitive decline increased by 34% (RR = 1.34, 95% CI = 1.16–1.55). Self-reported PD showed a lower risk of cognitive disorders compared with clinical classification (cognitive decline—RR = 0.77, 95% CI = 0.65–0.91; dementia/AD—RR = 0.86, 95% CI = 0.77–0.96). Conclusion: The prevalence and risk estimates of cognitive disorders in association with PD can be influenced by gender, the disease classification of PD and its severity. Further homologous evidence taking these study factors into consideration is needed to form robust conclusions.